Римское военное снаряжение из Херсонеса - Костромичев, Д.А. (Материалы по археологии, истории и этнографии Таврии, 2006)
Одной из составляющих истории римского военного присутствия в Херсонесе являются памятники материальной культуры. В отличие от военно-политической истории, материальная культура римского гарнизона города изучена еще довольно слабо. В первую очередь, это связано с проблемой поиска материальных свидетельств пребывания римлян на территории города. Такими свидетельствами, помимо хорошо изученных памятников эпиграфики, могут быть предметы, которыми владели римские военнослужащие. The article is devoted to the publication of details of Roman ammunition from Chersonesos Tauric excavation. This city is the most eastern point on the territory of Europe, where a garrison of Roman Army had been staying for several centuries. Forces to protect a town allied to the Empire were detached from the army in the province of Lower Moesia. The history of a Roman garrison is sufficiently well- known owing to the monuments of Latin epigraphy but up to nowadays material evidences of the Romans’ presence in the city have not been examined. 135 details of Roman military ammunition are collected in this publication.